Singlet oxygen-promoted one-pot synthesis of highly ordered mesoporous silica materials via the radical route. Issue 12 (7th June 2022) - Lu, Tingting; Yan, Wenfu; Feng, Guodong; Luo, Xiaolin; Hu, Yueqiao; Guo, Jiale; Yu, Zhan; Zhao, Zhen; Ding, Shujiang
Abstract : Compared with ˙OH in an acid-free synthesis system, 1 O2 plays a more important role in the hydrolysis of TEOS to meet the targeted assembly rate for templates, which is crucial for the one-pot synthesis of mesoporous silica materials. Abstract : The emergence of the free radical route has eliminated the need for a strong acid to catalyze the hydrolysis and condensation of silica species during the hydrothermal synthesis of highly ordered mesoporous silica materials. However, this approach is limited by low catalytic efficiency. Hence, the reaction process must be divided into two steps: hydrolysis and polymerization. Here, an acid-free green synthesis strategy was proposed for the one-pot synthesis of highly ordered mesoporous materials via the radical route with singlet oxygen promotion. The prepared materials exhibit a standard ordered mesoporous structure. Density functional theory calculations suggest that singlet oxygen cooperated with hydroxyl free radicals have higher catalytic activity than individual hydroxyl free radicals for tetraethyl orthosilicate hydrolysis. This synthesis approach overcomes the challenge in the direct one-pot acid-free synthesis of highly ordered materials and provides a facile and environmentally friendly route for the future large-scale production of ordered mesoporous materials.